Transformation of Islamic Boarding School Education: Dormitory Mapping Innovation to Print a Generation with Character and Independence - Ansori, Ansori; Sailin, Mujibus; Fahmi, Naufal; Azizi, Faiz; Masbahuddin, Masbahuddin (Universitas Nurul Jadid, 2023)
This research focuses on strategies to improve the quality of education at Nurul Jadid Islamic Boarding School through a dormitory mapping program. The main purpose of this study is to analyze how the dormitory mapping program can improve academic achievement, shape character, and develop students' spiritual independence. This study uses a qualitative method with a case study approach, where data is collected through in-depth interviews, observations, and document analysis from various related parties, including dormitory administrators, teachers, and students. The results of the study show that the dormitory mapping program has a significant impact on improving academic achievement, especially in difficult subjects such as mathematics and Arabic. In addition, the implementation of the curriculum in the dormitory has succeeded in shaping the character of discipline and spiritual independence of students through the habit of worship and daily activities. Structured extra-curricular programs also contribute to the development of non-academic skills such as technology and martial arts, which support the holistic development of students. The implications of this study emphasize the importance of structured dormitory management and the integration of educational programs that support holistic character and academic development. The dormitory mapping model implemented at the Nurul Jadid Islamic Boarding School can be used as a reference for other Islamic boarding schools who want to improve the quality of their education.